Salidroside Ameliorated Intermittent Hypoxia-Aggravated Endothelial Barrier Disruption and Atherosclerosis via the cAMP/PKA/RhoA Signaling Pathway - Li, Linyi; Yang, Yunyun; Zhang, Huina; Du, Yunhui; Jiao, Xiaolu; Yu, Huahui; Wang, Yu; Lv, Qianwen; Li, Fan; Sun, Qiuju; Qin, Yanwen (Frontiers in Pharmacology, 2021)
Background: Endothelial barrier dysfunction plays a key role in atherosclerosis progression. The primary pathology of obstructive sleep apnea-hypopnea syndrome is chronic intermittent hypoxia (IH), which induces reactive oxygen species (ROS) overproduction, endothelial barrier injury, and atherosclerosis. Salidroside, a typical pharmacological constituent of Rhodiola genus, has documented antioxidative and cardiovascular protective effects. However, whether salidroside can improve IH-aggravated endothelial barrier dysfunction and atherosclerosis has not been elucidated. Methods and results: In normal chow diet-fed ApoE-/- mice, salidroside (100 mg/kg/d, p.o.) significantly ameliorated the formation of atherosclerotic lesions and barrier injury aggravated by 7-week IH (21%–5%–21%, 120 s/cycle). In human umbilical vein endothelial cells (HUVECs), exposure to IH (21%–5%–21%, 40 min/cycle, 72 cycles) decreased transendothelial electrical resistance and protein expression of vascular endothelial cadherin (VE-cadherin) and zonula occludens 1. In addition, IH promoted ROS production and activated ras homolog gene family member A (RhoA)/Rho-associated protein kinase (ROCK) pathway. All of these effects of IH were reversed by salidroside. Similar to salidroside, ROCK-selective inhibitors Y26732 and Fasudil protected HUVECs from IH-induced ROS overproduction and endothelial barrier disruption. Furthermore, salidroside increased intracellular cAMP levels, while the PKA-selective inhibitor H-89 attenuated the effects of salidroside on IH-induced RhoA/ROCK suppression, ROS scavenging, and barrier protection. Conclusion: Our findings demonstrate that salidroside effectively ameliorated IH-aggravated endothelial barrier injury and atherosclerosis, largely through the cAMP/PKA/RhoA signaling pathway.